UPAYA MENINGKATKAN KECEPATAN MEMBACA DENGAN METODE GERAK MATA PADA SISWA KELAS V SD NEGERI 79 OKU - Sanjaya, M. Rama; Agustina, Aryanti (LPPM STKIP PGRI Bandar Lampung, 2017)
This research will discuss about the speed of reading with the method of eye movement on the fifth grade students of SD Negeri 79 OKU. This study aims to improve the speed of reading the the fifth grade students of SD Negeri 79 OKU by using the method of eye movement. This research is expected to be useful theoretically, the results of this study can provide an overview of efforts to increase the speed of reading with the method of eye movements on the fifth grade students of SD Negeri 79 OKU. In practice the reults of this study are expected to be useful for students, Indonesian language teachers. The method used ini this classroom action research is an experimental method. Data collection techniques used are observation and test, and data analysis technique with T test. Based on the results of this study concluded that the aplication of eye movement methods on subjects can improve student learning outcomes the fifth grade students of SD Negeri 79 OKU. This is marked by increasing the average value of student learning outcomes. The average increase of student learning outcomes in the pre cycle, that is 65,18 to 69,54 in cycle 1. 71,96 in cycle 2 end 74,47 in cycle 3. Thus the target is reached.